Dynamic features of speech and the characterization of speakers: Toward a new approach using formant frequencies - McDougall, Kirsty (International Journal of Speech, Language and the Law, 2006)
Previous research in speaker characteristics has tended to focus on static properties of the speech signal. Static features of speech generally display differences between individuals, but are insufficient to characterize a speaker. The present study considers reasons why dynamic features of speech should provide an important source of speaker-distinguishing information. It discusses this idea for formant frequencies in particular, and outlines a new direction for the development of a technique for characterizing individual speakers which uses regression to parameterize formant frequency contours. The technique is trialled and results reported for two data sets.